STRATEGIES FOR TEACHING WRITING SKILLS TO YOUNG LANGUAGE LEARNERS - Baymakova Sarvinoz Abdulaziz qizi, (TADQIQOTLAR, 2026)
Abstract: Learning to write in a new language is an essential skill, especially for young  learners  who  are  just  beginning  their  educational  journey.  Writing  not  only involves putting words on paper but also includes a range of cognitive and creative skills,  including  vocabulary  use,  sentence  structure,  grammar,  coherence,  and, significantly, motivation and confidence. Effective writing instruction can have a major impact on a child's academic development and communication abilities.